The comparison of physical and skills characteristic among elite youth rugby players in Malaysia / Dinie Afiq Mohd Zailani - Mohd Zailani, Dinie Afiq (Faculty of Sport Science and Recreation, 2016)
The purpose of the study was to determine the physical fitness and skills characteristic among elite youth rugby players in Malaysia. Twenty (n=20) rugby players from Sekolah Sukan Tunku Mahkota Ismail (SSTMI) and twenty-one (n=21) players from Sekolah Menengah Sains Machang (SMACH), age ranging 15 to 16 years old were recruited in this study. The anthropometric measurement Body Mass Index (BMI), physical fitness; power, agility, speed and maximal aerobic power and lastly for the skills characteristic; general, defending and evasion skills were measured. The results showed that there were no significant difference on power, maximal aerobic power, general skills and defending skills however there were significant different on agility, speed and evasion skills between SMACH and SSTMI. In conclusion, the physique and training volume influenced the results showed on this study where SSTMI showed better results in all testing components.